The development and validation of a family functioning measure for Aboriginal and Torres Strait Islander adults - Makayla-May Brinckley; Roxanne Jones; Philip J. Batterham; Alison L. Calear; Raymond Lovett (BMC, 2022)
Abstract Background Family and kinship networks are a key aspect of culture for Aboriginal and Torres Strait Islander peoples from Australia. They are intrinsically connected to good health and wellbeing, and cultural knowledge exchange. However, despite the known importance of family and kinship networks in Aboriginal and Torres Strait Islander cultures, and the move towards family-centred approaches in healthcare service provision, there is no validated, national measure of family functioning for Aboriginal and Torres Strait Islander peoples. A valid tool to measure family functioning is necessary in order to better understand what fosters good family functioning, and to inform and develop programs and healthcare interventions. Methods Mayi Kuwayu: the National Study of Aboriginal and Torres Strait Islander Wellbeing is a longitudinal cohort study of Aboriginal and Torres Strait Islander adults aged 16 years and over. An existing family functioning scale was modified for use in the Mayi Kuwayu Study to measure family functioning at the national Aboriginal and Torres Strait Islander population level. This study used a national sample of Aboriginal and Torres Strait Islander adults (N = 8705, ≥16 years) for the psychometric assessment of the modified Mayi Kuwayu Study Family Functioning Measure. This involved face validity, acceptability, internal consistency/reliability, construct validity, and convergent and divergent validity testing. Results Participants in this study were 8705 Aboriginal and Torres Strait Islander peoples, with a mean age of 48 years, who primarily live in regional Australia (47.3%). The Mayi Kuwayu Family Functioning Measure demonstrated face validity for family functioning and had good internal consistency/reliability (Cronbach's alpha > 0.90). Construct validity results were mixed, with an indication of uni-dimensionality (with one component explaining 59.5% of variance), but some item redundancy and inconsistency in responding patterns among groups of respondents. Balancing psychometric properties with Aboriginal and Torres Strait Islander expert and end-user feedback of the measure indicate that the full scale should be retained. Finally, the measure demonstrated strong convergent and divergent validity, with prevalence ratios exhibiting dose-response relationships between family functioning and conceptually related outcomes (convergent validity) and conceptually unrelated outcomes (divergent validity). Conclusion The Mayi Kuwayu Family Functioning Measure is a valid measure of family functioning in the Aboriginal and Torres Strait Islander adult population.